Investigating the molecular mechanism whereby auxin modulates Arabidopsis thaliana growth under salinity stress conditions - Ferrandi, Paul (Department of Molecular and Cell Biology, 2024)
Soil salinization is detrimental to plant growth and yield, and an increasing global problem in irrigated agricultural land. Salinity imposes both an osmotic and ionic stress on plants, the latter of which is unique to salt stress. Previous work has indicated that the plant growth hormone auxin could play an important role in ionic stress tolerance: transcriptome profiling revealed that the genes differentially expressed in response to ionic stress were enriched with the gene ontology term ‘Response to auxin'. Additionally, expression of the auxin biosynthesis gene, Nitrilase 2 (NIT2), was also specifically up-regulated in response to ionic stress. A NIT2 overexpressing line (35S::NIT2) has been shown to display improved germination and growth, as well as increased auxin levels compared to wild-type plants under saline conditions. The hypothesis thus is that salt stress induces NIT2 expression, thereby increasing auxin biosynthesis, which results in the activation of the plasma membrane (PM) H+-ATPase pump and subsequent activation of expansion growth mediated by expansins. Additionally, the pump activation could enhance the proton motive force for ion transport across the PM, thereby affecting ion homeostasis during salt stress. The aim of this study was to investigate this proposed molecular mechanism whereby auxin modulates plant growth in response to salt stress. Measurement of Na+ and K+ content revealed that 35S::NIT2 plants had improved root and shoot Na+/K+ ratios compared with wild-type (No-0 ecotype) plants, under saline conditions. This altered ion homeostasis might be a consequence of differences in the expression of several Na+ and K+ transporter/channel genes between the two lines. Of particular interest, under saline conditions, the 35S::NIT2 line had increased root HKT1;1, AKT1, and SKOR expression, as well as decreased GLR2.3 expression; and increased shoot NHX3, SOS1, and KUP1 expression. Together these results provide evidence that improved Na+/K+ homeostasis underlies the increased salinity tolerance of the 35S::NIT2 line. Proteomic analysis of enriched PM protein fractions isolated from the shoots of salt-stressed and untreated 35S::NIT2 and No-0 plants revealed genotype-specific differences in salt-responsive PM protein abundance, as well as differences between the two lines under both conditions. Gene ontology analysis revealed that several of the identified salt- responsive proteins were assigned with GO terms related to auxin and the ‘response to salt stress'. This included NIT2, which was up-regulated in response to salt in both 35S::NIT2 and No-0 plants, supporting the hypothesis that auxin biosynthesis is increased via NIT2 to modulate growth in saline conditions. Notably, far fewer salt-responsive proteins were identified in the 35S::NIT2 line than in No-0. A subset of the salt-responsive proteins identified in No-0 displayed higher constitutive expression in the 35S::NIT2 line under control conditions, and were not differentially expressed in response to salt (ERD7, PATL1, ABCC4, DRP2B). I propose that the processes that these proteins regulate, or are involved in, could be constitutively active in the 35S::NIT2 line, and that they could contribute to the increased salt- tolerance of the 35S::NIT2 line. This is the first report of salt-responsive changes in the PM proteome of Arabidopsis shoots, as well as the differences in the PM proteome of the 35S::NIT2 line that could contribute towards its improved salinity tolerance. Finally, Expansin 11 (EXPA11) was identified as a candidate growth effector acting downstream of auxin-induced PM H+-ATPase activation, as its expression was shown to be significantly higher in the 35S::NIT2 line than in No-0, and was further up-regulated in response to salt stress. Attempts to knock-down EXPA11 expression in the 35S::NIT2 line proved unsuccessful, with the transgenic 35S::EXPA11amiRNA lines not displaying any reduction in EXPA11 expression, or an altered phenotype. Transgenic lines overexpressing EXPA11 (35S::EXPA11) displayed increased hypocotyl elongation, improved seedling growth in untreated, salt, and osmotic stress conditions, and increased shoot fresh weight in older plants under saline conditions. Furthermore, the 35S::EXPA11 plants displayed a greater leaf surface area, with increased epidermal and palisade mesophyll cell areas. Collectively, these results indicate that EXPA11 plays a role in promoting growth in multiple tissues across different developmental stages, both in control conditions and in response to salt stress, and that overexpression of EXPA11 improves salinity tolerance by increasing shoot growth under saline conditions without causing a growth penalty under control conditions. Overall, this study presents evidence that NIT2 likely affects both ion homeostasis and plant growth through the auxin-induced activation of the PM H+-ATPase, and downstream growth modulating activity of EXPA11, during salt stress.